89x+56=67

Simple and best practice solution for 89x+56=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 89x+56=67 equation:


Simplifying
89x + 56 = 67

Reorder the terms:
56 + 89x = 67

Solving
56 + 89x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + 89x = 67 + -56

Combine like terms: 56 + -56 = 0
0 + 89x = 67 + -56
89x = 67 + -56

Combine like terms: 67 + -56 = 11
89x = 11

Divide each side by '89'.
x = 0.1235955056

Simplifying
x = 0.1235955056

See similar equations:

| 17=5x+5y | | 50-90x=89 | | Cos(8x)+cos(4x)+2cos(2x)=0 | | 45-89x=-78 | | 2v+2u+5u= | | 79x-76=90 | | x^2+20x+4800=0 | | 78x+76=89 | | x+84=-82 | | x-3=2(x-4) | | 34x-68=79 | | -18=3(3x-3) | | 5(5x+1)=-20 | | P^4-14p^2+40=0 | | -4x+28=-x+7 | | 57x-98=978 | | 45x+78=980 | | 45x+78=98 | | 2c^4-6c^3-12c^2+36c=0 | | 67x+34=173 | | 67x+34=67 | | 6x+43=55 | | 6x+43=45 | | 6x+43=345 | | 6x+43=34 | | 5x+8y=3965 | | 23x-5=34 | | 3x-y=10x+6 | | 5x-41=8x | | 75-30=45 | | (7x+4)(4x-7)= | | 25+75+-90=35 |

Equations solver categories